Ceiling of the Antarala of the Bhandasar Temple - Temples of India Project Team (Jio Institute, 2024)
Just above the beams of the antarala (antechamber), there is a strip or band that runs across the entire rectangular ceiling. This band has the depiction of twenty-four Tirthankara with their vahanas (rides). The Tirthankaras are drawn in their order, from viewers left to right all along the ceiling of the antechamber, starting with Rishabnath.